Low-molecular-weight heparin for the prevention of preeclampsia in high-risk pregnancies without thrombophilia: a systematic review and meta-analysis - Chen, Jiahui; Huai, Jing; Yang, Huixia (BMC pregnancy and childbirth, 2024)
To systematically evaluate the efficacy of low molecular weight heparin (LMWH) to prevent preeclampsia in high risk pregnant women without thrombophilia. PubMed, Embase and the Cochrane library were searched for articles published before 1st August 2022 using the combination keywords "preeclampsia", "Low Molecular Weight Heparin", "LMWH", "Heparin, Low Molecular Weight", "Dalteparin", "Nadroparin", and "Tinzaparin". Randomized controlled trials evaluating the use of LMWH in pregnant women at high risk of preeclampsia without thrombophilia. Ten studies were included in the meta-analysis (1758 patients in total). Outcomes were expressed as relative risk (RR) with 95% confidence intervals (CI). LMWH reduced the incidence of PE (RR = 0.67; 95% CI = 0.50-0.90; P = 0.009) in high risk pregnant women without thrombophilia. Subgroup analysis found that the prophylactic effect of LMWH was only significant in studies using low-dose aspirin (LDA) as the primary intervention. The combination of LMWH and LDA was also effective for the prevention of preterm birth and fetal growth restriction, but had no effect on the incidence of placenta abruption. For women at high risk of developing preeclampsia without thrombophilia, the combination of LMWH and low-dose aspirin is effective for the prevention of preeclampsia, preterm birth and fetal growth restriction and is superior to LDA alone.